Clinical features and survival in pulmonary Takayasu's arteritis associated pulmonary hypertension: a national registry study. (14th October 2021) - Zhu, Y.-J; Jiang, X; Peng, F.-H; Wang, L; Ma, W; Cao, Y.-S; Pan, X; Zhang, G.-C; Zhang, F; Fan, F.-L; Wu, B.-X; Huang, W; et al.
Abstract: Background: The clinical features and long-term outcomes of patients with pulmonary Takayasu's arteritis associated pulmonary hypertension (PTA-PH) have not been well studied. Purpose: To assess the clinical characteristics and long-term survival outcome in patients with PTA-PH. Methods: We conducted a multi-center cohort study using the clinical, functional, and hemodynamic data from the National Rare Diseases Registry System of China. Patients with Takayasu's arteritis and pulmonary artery involvement, who fulfilled the 1990 American College of Rheumatology and/or modified Ishikawa criteria, from 13 referral centers of China, were included. The diagnosis of pulmonary hypertension (PH) was confirmed by right heart catheterization findings. The primary outcome was time from diagnosis of PTA-PH to the occurrence of all-cause death. Results: Between Jan. 2007 and Jan. 2019, a total of 140 patients with PTA-PH were included, with a mean age of 41.4±14.3 years at diagnosis, and a female predominance (81%). The most common symptoms were exertional dyspnea (91%) and hemoptysis (36%). The majority of patients (87%) exhibited bilateral pulmonary artery involvement. Pulmonary lobar artery was the most frequently affected vessel (100%), followed by segmental artery (82%) and left/right pulmonary artery trunk (49%). Severely compromised hemodynamic profiles were identified in these patients, indicating by elevated mean pulmonary artery pressure (48, interquartile range [IQR] 38–59 mm Hg) and pulmonary vascular resistance (9.4, IQR 5.7–13.3 Wood U). The overall 1-year, 3-year, and 5-year survival rates in PTA-PH were 94.0%, 83.2%, and 77.2%, respectively (Figure). Predictors associated with increased risk of all-cause death were the presence of syncope (hazard ratio [HR]: 4.88; 95% CI: 1.62–14.74; p=0.005), N-terminal pro-B type natriuretic peptide level (HR: 1.04; 95% CI: 1.02–1.06; p<0.001), and right atrial pressure (HR: 1.07; 95% CI: 1.02–1.73; p=0.009). Conclusions: In this national registry study, the reported clinical features and long-term prognosis of patients with PTA-PH are novel findings. These findings may provide new insights on this specific pulmonary hypertension entity. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The National Key Research and Development Program of China